2009
DOI: 10.1111/j.1469-1795.2008.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level declines in Australian predators caused by an invasive species

Abstract: The cane toad Bufo marinus has been migrating westward across northern Australia since its introduction as a biological control agent in 1935. It has been implicated in the widespread decline of many native frog-eating predators. To investigate the impacts of this invasive species on native predatory reptiles, annual surveys were conducted from 2001 to 2007 to document variation in the relative abundances of three varanid lizards (Varanus mertensi, Varanus mitchelli and Varanus panoptes) and one crocodile Croc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
190
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(200 citation statements)
references
References 34 publications
5
190
2
Order By: Relevance
“…Given the extent of their reported direct impacts, we contend that it is likely that cane toads have also had indirect impacts on species which have strong interactions with species that have declined following the toad invasion. Indeed, given the multitude of possible indirect interaction pathways they could potentially disrupt (Doody et al 2009(Doody et al , 2013(Doody et al , 2015, we suspect that the invasion of cane toads has affected a much greater range of taxa than has thus far been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the extent of their reported direct impacts, we contend that it is likely that cane toads have also had indirect impacts on species which have strong interactions with species that have declined following the toad invasion. Indeed, given the multitude of possible indirect interaction pathways they could potentially disrupt (Doody et al 2009(Doody et al , 2013(Doody et al , 2015, we suspect that the invasion of cane toads has affected a much greater range of taxa than has thus far been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Direct population level impacts of cane toads have not been restricted to a single goanna species but a multitude of native predators in terrestrial and aquatic ecosystems including other monitor lizards, crocodiles, snakes and quolls (Shine 2010;. Doody et al (2006Doody et al ( , 2009Doody et al ( , 2013Doody et al ( , 2015 demonstrated that cane toad-induced decline of goannas can have cascading effects on species not predicted to be directly affected by cane toads such as small lizards, tree snakes, freshwater turtles and grain-eating birds in riparian systems in northern Australia. Cane toads have also been reported to have direct suppressive effects on their invertebrate prey, and to compete with nesting birds for burrows (Boland 2004;Greenlees et al 2007;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guild members are characterized as generalist, opportunistic predators possessing a degree of dietary overlap (Losos & Greene, 1988; Shine, 1986). The spread of the invasive cane toad ( Rhinella marinas ) has decreased populations of many varanid species across northern Australia (Doody et al., 2009; Doody, James, et al., 2014; Doody, Mayes, et al., 2014; Doody et al., 2017; Doody, Soanes, et al., 2015; Shine, 2010), potentially changing the nature of these guilds.…”
Section: Introductionmentioning
confidence: 99%
“…Often, though, abundance measurements are desired to monitor the longer-term dynamics of a population or focal suite of species. In particular, relative abundance data are important in identifying species in decline (Browne and Hecnar 2007;Doody et al 2009), the rise of invasive species (Engeman and Whisson 2006;Harrington et al 2008), the success of management strategies (Coelho and Manfrino 2007;Homyack and Haas 2009), as well as geographical differences in population dynamics (Okuda et al 2009). Presence data are already used to predict abundance in gridded plot surveys (Conlisk et al 2009).…”
Section: Introductionmentioning
confidence: 99%